Remembering National Socialism in Austrian Post-war Film (1945-1955) - Gortat, Jakub, (Amsterdamer Beiträge zur neueren Germanistik ;, 2025)
Entrenched in the myth of being victim of the Nazi aggression, Austrian elites pursued a politics of memory that symbolically shook off any responsibility for the emergence, development and consequences of National Socialism. Authors of the vast majority of films produced early after 1945 were not interested in dealing with the recent Nazi past of their country. There were, however, exceptions. Through detailed analysis of the narratives, stylistic patterns and reception of films that were set during or immediately after World War II, this book explains how cinema corroborated Austrian national self-stereotypes, at the same time offering a critique of the Nazi regime.